2019
DOI: 10.1021/jacs.9b06036
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Membrane Receptors: Norovirus Detachment via Lectin Attachment

Abstract: Virus internalization into the host cells occurs via multivalent interactions, in which a single virus binds to multiple receptors in parallel. Because of analytical and experimental limitations this complex type of interaction is still poorly understood and quantified. Herein, the multivalent interaction of norovirus-like particles (noroVLPs) with H or B type 1 glycosphingolipids (GSLs), embedded in a supported phospholipid bilayer, is investigated by following the competition between noroVLPs and a lectin (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…CSPs were observed as far as 25 Å from the HBGA binding pocket at ligand saturation, suggesting the presence of an allosteric network regulated by HBGA binding. A recent study monitored the binding of human norovirus virus-like particles to glycosphingolipids embedded in a phospholipid bilayer (Parveen et al 2019). From competitive titrations, it was concluded that the intrinsic (per binding site) bond energies of H type 1 and B type 1 glycosphingolipids are in good agreement with the K D s reported for HBGAs by NMR.…”
Section: Biological Contextmentioning
confidence: 68%
“…CSPs were observed as far as 25 Å from the HBGA binding pocket at ligand saturation, suggesting the presence of an allosteric network regulated by HBGA binding. A recent study monitored the binding of human norovirus virus-like particles to glycosphingolipids embedded in a phospholipid bilayer (Parveen et al 2019). From competitive titrations, it was concluded that the intrinsic (per binding site) bond energies of H type 1 and B type 1 glycosphingolipids are in good agreement with the K D s reported for HBGAs by NMR.…”
Section: Biological Contextmentioning
confidence: 68%
“…By solving the rate equations of CTxB binding and SV40 release and by using estimates for the maximum valency obtainable by SV40 on a planar membrane, it was possible to relate the observed release kinetics with the binding strength of the single VP1-GM1 pair. In a follow-up study, Parveen et al [ 78 ] applied the same methodology to probe binding of human norovirus VLPs to histo-blood group antigens (HBGAs) presented on GSLs and release of these VLPs from the HBGAs upon addition of a lectin from Ralstonia solanacearum (Fig. 3A, B ).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…As the friction strongly depends on the size of the adsorbed object, it is possible to distinguish binding events caused by viruses and proteins and thus to probe the release of membrane-bound viruses upon addition of a binding competitor having a higher affinity to the receptor/attachment factor (e.g., a lectin). This provides information on the binding strength of the virus-membrane interaction and (B) on the accumulation of receptors/attachment factors by the virus, which generates deviations between the relative virus surface coverage, determined during the initial binding process (B, solid line) or lectin-induced virus release (B, circles) [ 78 ]. (C) TIRF microscopy can be used to probe the binding of receptor/attachment factor-containing, dye-labeled vesicles and interface-linked viruses, allowing to determine the impact of the constituents (e.g., vesicle composition or virus strain) on the overall interaction.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Still, the rich information contained in combined ∆f n and ∆D n measurements, especially when combined with theoretical models representing the response for viscoelastic films, 9,10 has turned out very valuable in multiple research areas, including hydration analysis of organic polymers 11,12 , proteins 13 and biological membranes 13,14 . The method is also widely applied to investigate material porosity 15,16 , growth of mesoporous material 17 , characterization of biomimetic membranes 18,19 , development of bioanalytical sensors [20][21][22][23] , as well as in studies of biomolecular interactions 24,25 , including interrogations of their structural 26 and orientational 27 changes.…”
mentioning
confidence: 99%